FAKTOR PENDORONG PEMBUATAN PAKTA AUKUS: ANALISA GEOPOLITIK DI KAWASAN ASIA PASIFIK - dewi, ni putu ari sawitri; Parameswari, A.A. Ayu Intan; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
Abstract This study examines the factors that influenced the creation of the AUKUS pact, which is seen from the security complexities of the Asia Pacific region through the perspective of the United States. Asia Pacific is a strategic and distinguished regional which though it has been potential regional , Asia Pacific also contains several problems such as territorial conflict of South China Sea by the countries in this region and also there is power competition between United States and China. United States tried to restain China’s power through AUKUS pact. This research aim to analyze the push factors of AUKUS pact. This research also uses qualitative method. As for, the result of research is there are four variables i.e boundary, anarchy structure, polarity and social contruction which is only boundary can not be fulfilled. Keywords : United States, AUKUS, Asia Pacific, Regional Security Complexity Theory, and Regional Study.